PENGEMBANGAN MULTIMEDIA INTERAKTIF IPA TERPADU MENGGUNAKAN MACROMEDIA FLASH UNTUK PEMBELAJARAN IPA DI KELAS VII MATERI USAHA DAN ENERGI - Sigit Lubai; Nyoman Erosa; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
This study aimed to describe (1) the development of interactive multimedia of science subject by using macromedia flash and (2) the quality of interactive multimedia of science subject in energy and effort material. The type of this study was research and development. The research instrument was questionnaire. Data analyzing techniques were conducted by (1) tabulating data, 2) calculating the average score, and 3) changing the average score based on score category. Based on the result of product testing through expert of media, developing interactive multimedia by using macromedia flash in the teaching of energy and effort material that were seen from aspects of media features and organization were very good. The grading of learning media based on the aspect of teaching and material based on material expert was very good. The result of product testing by the teacher of science subject that was seen from aspects of teaching, material, media features, and the use was very good. The result of product teaching by the seventh grade students of SMP that was seen from aspects of teaching, material, feature, media, and the use was very good. Based on those descriptions, it could be concluded that teaching media of science subject by using macromedia flash was effective and efficient as the teaching tool for the teacher in the teaching and learning process.